Reconstructing the Philosophy of Science in Islamic Educational Management: Theoretical Foundations and Contemporary Challenges - Shobri, Muwafiqus; Wijaya, Mohamad Sugi; Ermansyah, KMS; Sujarwo, Agus (UII Darullughah Waddawah Pasuruan, 2026)
The development of Islamic educational management is confronted with increasingly complex conceptual challenges driven by globalization, digital transformation, and the growing demand for modern educational governance, thereby necessitating a strong and contextually grounded philosophical foundation. This article aims to reconstruct the philosophy of science underlying Islamic educational management as a theoretical framework capable of addressing contemporary challenges while remaining firmly rooted in Islamic values. The study employs a qualitative approach through a literature-based inquiry using narrative review and integrative review strategies, enriched by critical philosophical analysis of relevant scholarly publications in the fields of philosophy of science, educational management, and Islamic education. The findings reveal that existing theories and practices of Islamic educational management remain largely fragmented, with a dominant reliance on modern managerial paradigms that have not been fully integrated with Islamic ontological, epistemological, and axiological dimensions. A philosophical reconstruction is therefore required to reaffirm an Islamic educational ontology centered on the concept of insan kamil, an integrative epistemology that synthesizes revelation, rational inquiry, and empirical experience, and an axiology that positions tauhid, justice, and maslahah as the core orientations of educational management. This article contributes to strengthening the theoretical foundation of Islamic educational management by offering a holistic and contextual conceptual framework, while also providing strategic implications for the development of more adaptive, ethical, and sustainable managerial policies and practices within Islamic educational institutions in the contemporary era.